Fiscal Horizontal Transfers and Fiscal Autonomy in Local Government: Evidence of Public-Private-Partnership influence in Uganda (Global Journal of Management and Business Research, 2019)
Drawing on the pure theory of local expenditure and fiscal federalism theory, we investigated whether fiscal horizontal transfers are antecedents of fiscal autonomy in local government. Moreover, it was also examined if public-private-partnerships possibly mediate the fiscal horizontal transfers-fiscal autonomy relationship. In order to test the hypothesized model, data were collected from 27 districts, 9 municipalities and 243 sub-counties scattered in the eastern region of Uganda, East Africa. Over the years, the country has been applauded for its relatively efficient fiscal federalism system in the region. Data were then subjected to both regression and structural equation modeling statistical analysis. Results indicated that fiscal horizontal transfers predict changes in fiscal autonomy and public-privatepartnerships have an intervening influence on the fiscal horizontal transfers-fiscal autonomy linkages. Implications to both theory and practice are accordingly discussed and future research path is proposed.
Keywords: local government; fiscal horizontal transfers; fiscal autonomy; public-private partnerships